Grasping things : folk material culture and mass society in America - Bronner, Simon J. (University Press of Kentucky, 1986)
America stocks its shelves with mass-produced goods but fills its imagination with handmade folk objects. In Pennsylvania, the ""back to the city"" housing movement causes a conflict of cultures. In Indiana, an old tradition of butchering turtles for church picnics evokes both pride and loathing among residents. In New York, folk-art exhibits raise choruses of adoration and protest. These are a few of the examples Simon Bronner uses to illustrate the ways Americans physically and mentally grasp things. Bronner moves beyond the usual discussions of form and variety in America's folk material cu